Abnormal posterior semicircular canal function may predict poor prognosis in patients with severe and profound ISSNHL - Yang, Yang; Gao, Dekun; Ma, Xiaobao; Shen, Jiali; Zhang, Qin; Chen, Xiangping; Zhang, Qing; Jin, Yulian; Chen, Jianyong; Duan, Maoli; Yang, Jun (Frontiers in Neurology, 2023)
Background Severe and profound idiopathic sudden sensorineural hearing loss (ISSNHL) generally leads to unfavorable prognosis, and has a considerable impact on patient quality of life. However, related prognostic factors remain controversial. Objective To elaborate the relationship between vestibular function impairment and the prognosis of patients with severe and profound ISSNHL, and investigated the relevant factors affecting prognosis. Methods Forty-nine patients with severe and profound ISSNHL were divided into good outcome group [GO group, pure tone average (PTA) improvement > 30 dB] and poor outcome group (PO group, PTA improvement ≤ 30 dB) according to hearing outcomes. The clinical characteristics and the proportion of abnormal vestibular function tests in these two groups were analyzed by univariate analysis, and multivariable logistic regression analysis was performed for parameters with significant differences. Results Forty-six patients had abnormal vestibular function test results (46/49, 93.88%). The number of vestibular organ injuries was 1.82 ± 1.29 in all patients, with higher mean numbers in PO group (2.22 ± 1.37) than in GO group (1.32 ± 0.99). Univariate analysis revealed no statistical differences between the GO and PO groups in terms of gender, age, side of the affected ear, vestibular symptoms, delayed treatment, instantaneous gain value of horizontal semicircular canal, regression gain value of vertical semicircular canal, abnormal rates of oVEMP, cVEMP, caloric test and vHIT in anterior and horizontal semicircular canal, however, significant differences were found in the initial hearing loss and abnormal vHIT of posterior semicircular canal (PSC). Multivariable analysis revealed that only PSC injury was an independent risk factor for predicting the prognosis of patients with severe and profound ISSNHL. Patients with abnormal PSC function had worse initial hearing impairment and prognosis than patients with normal PSC function. The sensitivity of abnormal PSC function in predicting poor prognosis in patients with severe and profound ISSNHL was 66.67%, specificity was 95.45%, and positive and negative likelihood ratios were 14.65 and 0.35, respectively. Conclusion Abnormal PSC function is an independent risk factor for poor prognosis in patients with severe and profound ISSNHL. Ischemia in the branches of the internal auditory artery supplying the cochlea and PSC may be the underlying mechanism.